Anatomy and physiology for nursing and health professionals - Colbert, Bruce J. , 1958-; Ankney, Jeff; Lee, Karen T. (Harlow, England ; New York : Pearson Education, 2009)
"With an applied, visual approach, this book covers the structure and functions of the human body - and clinical applications throughout show the relevance of that knowledge in clinical practice. Contains terminology guides, amazing body facts (to give you an appreciation of just how amazing the human design is), and learning hints - as well as advice study skills and stress management tips; Case studies show how the material might present itself in clinical practice; An engaging writing style helps to explain the most difficult concepts; and Check out the companion website at www.pearsoned.co.uk/colbert, where you'll find further exercises and animations to help you on your way. A clear, straightforward book on anatomy and physiology for all students in nursing and allied health professions."--BOOK JACKET
Includes bibliographical references and index
Keywords: Human anatomy; Physiology; Anatomy; Physiological Phenomena